Requirements for the Transition to School-Based Management in Secondary Schools from the Perspective of School Administration (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
This study aims to identify the requirements for transitioning to self-management in secondary schools in Latakia from the perspective of school administrators (principals and vice-principals) and to examine the significance of differences based on educational qualification and years of service. The research employed a descriptive-analytical method, with a sample of 106 school administrators. A 32-item questionnaire covering four main domains—administrative and organizational, human, financial, and technical requirements—was developed and validated for reliability.Results indicated that administrative and organizational requirements ranked highest in importance, followed by financial, human, and finally technical requirements. No statistically significant differences were found based on educational qualification, except for administrative and organizational requirements favoring holders of a teaching qualification diploma. Similarly, no significant differences were attributed to years of service. The study recommends enhancing practical training programs for administrators, developing supportive financial and technical mechanisms to facilitate the transition to self-management, promoting awareness and continuous evaluation, and conducting future research in this field.
Keywords: School-Based Management, self-management, transition to self-management. Requirements for the transition to self-management.